PENERAPAN MODEL DISCOVERY LEARNING UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SDN 003 LUBUK OGONG KECAMATAN BANDAR SEIKIJANG - Fadliati, Fadliati; Munjiatun, Munjiatun; Alpusari, Mahmud (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The problem is undelined by the low of the result of science study in IPA learning. This is caused by the lack of the teacher’s knowledge toward IPA learning concept, teacher is still using speech method in teaching and learning process. The students are rerely given opportunity in searching and improving of the thinking ability to build knowledge and experience of learning. To solve the problem, Discovery Learning Model can improve the result of science study on the fifth grade students of SD Negeri 003 Lubuk Ogong. The subject of the research is the fifth grade students of SD Negeri 003 Lubuk Ogong of year academic of 2014/2015, with 26 students. This research used Class Action Research Method design which is done twice cycles. Each cycle is applied in twice with once of examination at the end of the cycle that aimed to improve the result of science learning of the fifth grade students of SD Negeri 003 Lubuk Ogong on the Sifat-sifat Cahaya subject. The result of result shows that the implied of the Discovery Learning Design can improve the science study of the fifth grade students of SD Negeri 003 Lubuk Ogong. The basic score is 49,80, then on the cycle I it increases to 69,04 from the basic score, and increases to 78,85 then cycle I in cycle II. The explaination above can be cancluded that aplication of Discovery Learning Model can improve the result of science study of fifth grade of SD Negeri 003 Lubuk Ogong Kecamatan Bandar Seikijang Kabupaten Pelalawan.Key words: Discovery Learning, the result of science study learning